Rethinking the New Medievalism - Bloch, R. Howard 1943-; Calhoun, Alison 1979-; Cerquiglini-Toulet, Jacqueline 1945-; Küpper, Joachim 1952-; Patterson, Jeanette (Johns Hopkins University Press, 2014)
Cover -- Contents -- Introduction. The New Philology Comes of Age -- 1 New Challenges for the New Medievalism -- 2 Reflections on The New Philology -- 3 Virgil's "Perhaps": Mythopoiesis and Cosmogony in Dante's Commedia (Remarks on Inf. 34, 106-26) -- 4 Dialectic of the Medieval Course -- 5 Religious Horizon and Epic Effect: Considerations on the Iliad, the Chanson de Roland, and the Nibelungenlied -- 6 The Possibility of Historical Time in the Crónica Sarracina -- 7 Good Friday Magic: Petrarch's Canzoniere and the Transformation of Medieval Vernacular Poetry -- 8 The Identity of a Text